2015
DOI: 10.1039/c4nr06037g
|View full text |Cite
|
Sign up to set email alerts
|

Capacious and programmable multi-liposomal carriers

Abstract: Spherical polycationic brushes (SPBs) were synthesized by grafting polycationic chains onto 100 nm polystyrene particles. These particles were exposed to unilamellar egg-lecithin (EL) liposomes with a mean diameter of 40 nm that had been rendered anionic via the presence of 10 molar% of phosphatidylserine (PS(1-)). The liposomes also contained 30 mole% of a morpholinocyclohexanol-based lipid (MOCH) that undergoes a conformational flip when the pH is decreased from 7.0 to 5.0. Mixtures of SPBs and liposomes at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 42 publications
(61 reference statements)
1
17
0
Order By: Relevance
“…For example, Leblond and co‐workers reported a bis‐(methoxyphenyl)pyridine system in which protonation of the central pyridine nitrogen leads to rotation of methoxyphenyl groups to promote hydrogen bonding, thereby disrupting the membrane and triggering release . Additionally, Menger and co‐workers reported a morpholinocyclohexanol‐ (MOCH)‐lipid that undergoes a cyclohexanol chair flip upon morpholine protonation to help trigger release when the liposomes are tethered to spherical polycationic brushes . Regarding release driven by binding interactions, Smith and co‐workers utilized a sensor that targets the lipid phosphatidylserine (PS) to trigger release from liposomes containing PS .…”
Section: Resultsmentioning
confidence: 99%
“…For example, Leblond and co‐workers reported a bis‐(methoxyphenyl)pyridine system in which protonation of the central pyridine nitrogen leads to rotation of methoxyphenyl groups to promote hydrogen bonding, thereby disrupting the membrane and triggering release . Additionally, Menger and co‐workers reported a morpholinocyclohexanol‐ (MOCH)‐lipid that undergoes a cyclohexanol chair flip upon morpholine protonation to help trigger release when the liposomes are tethered to spherical polycationic brushes . Regarding release driven by binding interactions, Smith and co‐workers utilized a sensor that targets the lipid phosphatidylserine (PS) to trigger release from liposomes containing PS .…”
Section: Resultsmentioning
confidence: 99%
“…The number of liposomes capable of complexing with a single particle ( N ) was estimated using a relation derived earlier: N=Clip×S1×NA×D3×ρ6Ccar×d2×M where C lip is the lipid concentration at saturation (0.2 mg mL −1 ), S 1 is the mean surface area per lipid molecule or 0.7 nm 2 , d is the diameter of liposomes, M is the mean molecular weight of lipid, C car is the carrier (PLAM) concentration, D is the diameter of the polylactide core and ρ is its density, and N A is the Avogadro number. Substituting the experimental values and literature data into Eqn (1) gave N = 30, which is to say that an average of 30 liposomes bind to each polylactide micelle.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, cryo‐EM studies showed considerable membrane defects and budding at lower pH. In work since this initial report, the basicity of the amine group has been varied, the mechanistic details of release have been further studied, incorporation into liposomes has been shown to enhance gene delivery, libraries of compounds with different properties have been studied and compared, and this system has been combined with spherical polycationic brushes for pH‐driven release from these nanoparticles …”
Section: Ph‐responsive Lipid Switchesmentioning
confidence: 99%
“…In work since this initial report, the basicity of the amine group has been varied, [10] the mechanistic details of release have been further studied, [11] incorporation into liposomes hasbeen shown to enhance gene delivery, [12] libraries of compounds with different properties have been studied and compared, [13] and this system has been combined with spherical polycationic brushes for pH-driven releasefrom these nanoparticles. [14] LeBlond and co-workersh ave investigated pH-responsive lipid switchesb ased on ad i(methoxyphenyl)pyridine scaffold. [15] These wered esigned such that protonation of pyridine of initial conformer 2a would trigger rotation of the substituted anisole rings resultingi nh ydrogen bonding betweent he methoxya nd pyridinium groups in 2b (Scheme 3).…”
Section: Ph-responsive Lipid Switchesmentioning
confidence: 99%